Temporal changes in ewe vaginal microbiota throughout gestation - Cassas, Mackenzie S.; Jonas, Lucille C.; Anderson, Chiron J.; Schmitz-Esser, Stephan; Youngs, Curtis R. (Frontiers in Microbiology, 2024)
Numerous factors are known to influence reproductive efficiency in ewes, but few studies have investigated the potential role of vaginal microbiota in sheep reproductive success. The objective of this study was to thoroughly characterize the ewe vaginal microbiota throughout the course of pregnancy. Vaginal samples were collected from 31 pregnant Hampshire and Hampshire X Suffolk crossbred ewes on a weekly basis from pre-breeding to pregnancy testing and then biweekly until just after lambing. To characterize the vaginal microbial communities, DNA was extracted and 16S rRNA gene Illumina MiSeq amplicon sequencing was performed. Alpha diversity metrics indicated an increase in species richness, evenness, and overall diversity throughout gestation. Distinct shifts in the bacterial communities were observed during gestation and were segregated into three periods: early gestation, a transitional period and late gestation. During early gestation, Actinobacillus, Histophilus, and unclassified Leptotrichiaceae were found in greater relative abundance. During the transitional period, a population shift occurred characterized by increasing relative abundance of Streptococcus and Staphylococcus. During late gestation, Staphylococcus, Streptococcus, and Ureaplasma had the greatest relative abundance. These shifts in the microbial population throughout the ewe's gestation are likely related to hormonal changes triggered by the growing conceptus, specifically increasing blood concentration of progesterone. The transitional period shift in vaginal microbial communities potentially aligns with the placental take-over of progesterone production from the corpus luteum at approximately day 50 after conception (gestational week 7). Understanding the observed variability of the vaginal microbiota throughout pregnancy will allow for future comparison of ewes that did not become pregnant or had abnormal pregnancies, which could lead to the discovery of potential bacterial biomarkers for pregnancy outcome; this understanding could also lead to development of probiotics to improve sheep reproductive success.